2003
DOI: 10.1180/0026461036740126
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of a high-T hydrothermal dolostone from the Emirli (Ödemiş, western Turkey) Sb-Au deposit

Abstract: A dolostone layer is found in spatial association with the Emirli epithermal Sb-Au deposit in western Turkey. It occurs within an argillic alteration zone adjacent to the major Emirli fault zone, which is the controlling structure for the deposit, and is composed of large closely packed subhedral to anhedral planar and nonplanar dolomites. Pyrite is the only accessory mineral in the layer and occurs as disseminations and veinlets up to 100 μm wide. Dolomite crystals are petrographically homogeneous and have co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…These new data on the mineral compositions of carbonates clearly support the idea previously described that Mn can be used a as whole-rock element index of hydrothermalore bearing activity (e.g., [18,19]) and previous studies that showed elevated concentrations of Mn (and Fe) in carbonates related to precious and base-metal hydrothermal deposits (e.g., [6,[15][16][17]). In contrast, where the carbonates are paragenetically late or unrelated to the mineralization, they show markedly lower Mn contents (0.00-0.08 at.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These new data on the mineral compositions of carbonates clearly support the idea previously described that Mn can be used a as whole-rock element index of hydrothermalore bearing activity (e.g., [18,19]) and previous studies that showed elevated concentrations of Mn (and Fe) in carbonates related to precious and base-metal hydrothermal deposits (e.g., [6,[15][16][17]). In contrast, where the carbonates are paragenetically late or unrelated to the mineralization, they show markedly lower Mn contents (0.00-0.08 at.…”
Section: Discussionsupporting
confidence: 86%
“…Carbonates are a focus of interest to researchers investigating ore-forming systems; fluid inclusion and isotopic data (C, O, Sr, Pb) can give important information on the provenance of hydrothermal fluids (e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13]). However, only limited works on the composition of carbonates in ore-forming hydrothermal environments are available (e.g., [6,[14][15][16][17]). Nevertheless, these authors suggest a possible association of an elevated Mn content in carbonates with ore-forming hydrothermal fluids, and Mn has been used as an index of such activity in whole-rock compositions (e.g., [18,19]).…”
Section: Introductionmentioning
confidence: 99%
“…This is slightly different from the marine dolomite, which commonly has 110-160 ppm Na (Veizer, 1983;Qing and Mountjoy, 1988). The high Na concentrations may be due to the presence Na in fluid inclusion (Akcay et al, 2003). Additionally, the Na-content of the cortex is slightly higher than that of the cores (Fig.…”
Section: Major Element and Trace Elementmentioning
confidence: 92%
“…Meta-sedimentary type Pb-Zn mineralizations are Triassic-aged and formed before metamorphism. The vein-type lead-zinc mineralizations were most likely emplaced along the NE–SW kink lines due to granodioritic intrusions in the Early-Middle Miocene interval . The main mineralization in the Ödemiş-Kiraz Submassif in the region is on the main faults in the E-W direction.…”
Section: Geological and Hydrogeological Settingsmentioning
confidence: 98%